Mitochondrial DNA variants segregate during human preimplantation development into genetically different cell lineages that are maintained postnatally. Issue 21 (14th March 2022) - Mertens, Joke; Regin, Marius; De Munck, Neelke; Couvreu de Deckersberg, Edouard; Belva, Florence; Sermon, Karen; Tournaye, Herman; Blockeel, Christophe; Van de Velde, Hilde; Spits, Claudia
Abstract: Humans present remarkable diversity in their mitochondrial DNA (mtDNA) in terms of variants across individuals as well as across tissues and even cells within one person. We have investigated the timing of the first appearance of this variant-driven mosaicism. For this, we deep-sequenced the mtDNA of 254 oocytes from 85 donors, 158 single blastomeres of 25 day-3 embryos, 17 inner cell mass and trophectoderm samples of 7 day-5 blastocysts, 142 bulk DNA and 68 single cells of different adult tissues. We found that day-3 embryos present blastomeres that carry variants only detected in that cell, showing that mtDNA mosaicism arises very early in human development. We classified the mtDNA variants based on their recurrence or uniqueness across different samples. Recurring variants had higher heteroplasmic loads and more frequently resulted in synonymous changes or were located in non-coding regions than variants unique to one oocyte or single embryonic cell. These differences were maintained through development, suggesting that the mtDNA mosaicism arising in the embryo is maintained into adulthood. We observed a decline in potentially pathogenic variants between day 3 and day 5 of development, suggesting early selection. We propose a model in which closely clustered mitochondria carrying specific mtDNA variants in the ooplasm are asymmetrically distributed throughout the cell divisions of the preimplantation embryo, resulting in the earliest form of mtDNA mosaicism in human development.